La fase final de unas migraciones de larga duración: gallegos hacia Buenos Aires (1946-1960) - Nadia Andrea De Cristóforis (Amnis)
Throughout this article, we will try to provide some research results for the understanding of the last cycle of Galician immigration in Argentina, namely, the one that took place between 1946 and 1960, approximately. We will concentrate on the following aspects: the quantitative dimensions of these currents and its rhythms of displacement; the areas of departure of migrants and the conditions of overseas flows, in different scales of analysis. We will also try to identify the migratory mechanisms favoring researched migratory processes, both spontaneous and official. Finally, we will postulate that the migrations of Galicians to Buenos Aires, after the Second World War, developed with a high degree of autonomy, with respect to the prevailing normative, institutional and political frameworks on both sides of the Atlantic Ocean.For this study we have used the following sources: migration statistics of the Ministerio de Trabajo (Spain) and the Dirección Nacional de Migraciones (Argentina); libros de desembarco, actas de inspección marítima and official documents on migratory policies of peronism (Archivo General de la Nación, Buenos Aires); records of the Comisión Católica Española de Migración de La Coruña (Arquivo da Emigración Galega, Santiago de Compostela); documents of the Archivo General de la Administración (Alcalá de Henares) and the Archivo del Ministerio de Asuntos Exteriores (Madrid); newspapers of the time (Faro de Vigo or Nuevo Correo, among others) and writings of officials and politicians from the mid-20th century (Martí Bufill or Vicente Borregón Ribes).